Measuring the Trends in Inequality of Individuals and Families: Income and Consumption - Fisher, Jonathan D; Johnson, David S; Smeeding, Timothy M (American Economic Review, 2013)
We present evidence on the level of and trend in inequality from 1985-2010 in the United States, using disposable income and consumption for a sample of individuals from the Consumer Expenditure (CE) Survey. Differing from the findings in other recent research, we find that the trends in income and consumption inequality are broadly similar between 1985 and 2006, but diverge during the Great Recession with consumption inequality decreasing and income inequality increasing. Given the differences in the trends in inequality in the last four years, using both income and consumption provides useful information.